Kosten der Kleinheit und die Föderalismusdebatte in der Schweiz - Kersten Kellermann (Universität Liechtenstein, Konjunkturforschungsstelle Liechtenstein (KOFL), 2007)
This paper discusses the smallness of subsidiary jurisdictions as a third dimension of centrality, besides vertical centrality and fragmentation (horizontal centrality). A panel analysis concerning all 26 Swiss cantons (from 1990 to 2003) shows that public expenditure per-capita increases with the number of inhabitants of a canton. This holds for the aggregate expenditure level and for 6 expenditure categories of the Government Finance Statistics. The positive elasticity of per-capita expenditure with respect to population size can be understood as an indicator for increasing government failure in jurisdictions with bigger population size.
Keywords: H40; H72; H77; 330; Kosten der Kleinheit; Skaleneffekte; Dezentralität; Einwohnerelastizität; Öffentliche Ausgaben; Föderalismus; Leviathan-Hypothese; Föderalismus; Öffentliche Ausgaben; Skalenertrag; Dezentralisierung; Leviathan-Modell; Schätzung; Schweiz